Moments of speaking and silencing: Nurses share their experiences of manual handling in healthcare. Issue 1 (March 2015) - Kay, Kate; Evans, Alicia; Glass, Nel
Summary Nursing care involves complex patient handling tasks, resulting in high musculoskeletal injury rates. Epidemiological studies from the 1980s estimated a lifetime prevalence of lower back injuries for nurses between 35 and 80%. National and international studies continue to mirror these findings. Despite the development of programs intended to reduce manual handling injuries, sustainable solutions remain elusive. This paper reports on a study of nurses speaking about their perspectives on current manual handling practices. Qualitative research conducted in 2012 investigated nurses' perceptions and experiences relating to manual handling in the healthcare context and their participation in injury prevention programs. There were two research methods: semi-structured interviews and researcher reflective journaling. The research was framed in critical emancipatory methodology. Thirteen nurses from two Australian states participated in the study. Thematic analysis revealed an overarching theme of 'power relations' with a subcategory of '(mis)power' that comprised two subthemes, these being 'how to practice' and 'voicing practice issues'. Specifically, this paper explores nurses verbalising their views in the workplace and responses which left them feeling silenced, punished and disillusioned. The findings suggest that the socio-political context within which nurses practice impacts upon their ability to voice concerns or ideas related to manual handling. Inclusion of nurses in the manual handling dialogue may generate an expanded understanding of, and the potential to transform, manual handling practices in healthcare environments.